2001
DOI: 10.1002/ajh.1190
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and molecular characterization of a patient with simultaneous B‐cell chronic lymphocytic leukemia and peripheral T‐cell lymphoma

Abstract: A patient is described who developed a peripheral T-cell lymphoma (PTCL) after a 6-year history of B-cell chronic lymphocytic leukemia (B-CLL). The progression of the T-cell disease spreading to pleura and skin terminated the course of the disease. A cytogenetic analysis performed six years after the ®rst onset of the B-CLL showed the presence of two clones, one with trisomy 12 and another with inv(14)(q11q32.1) and trisomy 8. Combined immunophenotyping and¯uorescence in situ hybridization demonstrated that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…From the clonality study examining two representative patients we have shown that these tumors may arise either from a single clone or from multiple clones of T cells. Our findings that different types of lymphoid neoplasms can occur in a patient, simultaneously or subsequently, correspond to previous reports on EBV‐associated T‐cell and B‐cell neoplasms 2,21,52 . For the pathogenic mechanism of the EBV‐associated peripheral T‐cell proliferative disease/lymphoma, we postulate that the EBV that is dormant in the latently EBV‐infected B cells may infect many subsets of T cells.…”
Section: Discussionsupporting
confidence: 89%
“…From the clonality study examining two representative patients we have shown that these tumors may arise either from a single clone or from multiple clones of T cells. Our findings that different types of lymphoid neoplasms can occur in a patient, simultaneously or subsequently, correspond to previous reports on EBV‐associated T‐cell and B‐cell neoplasms 2,21,52 . For the pathogenic mechanism of the EBV‐associated peripheral T‐cell proliferative disease/lymphoma, we postulate that the EBV that is dormant in the latently EBV‐infected B cells may infect many subsets of T cells.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to most of the PTCLs previously encountered, 2 of our 3 patients had ALK + ALCL, both occurring in women. 19 The clinical features of our 3 cases and of other cases of PTCL in CLL patients 6,18,[20][21][22][23][24][25][26][27][28][29][30] are summarized in Tables 1 and 3. One additional case of ALK + ALCL arising in a patient with CLL/SLL has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…PTCLs in CLL/SLL Patients: Review of Literature study had limited-stage disease and responded well to therapy, in contrast to most other PTCL. A previously described case of composite SLL and CD4 + PTCL was shown to be genetically distinct on the basis of the identification of trisomy 12 limited to the SLL cells and trisomy 8 limited to the CD4 + T cells 25. Another consideration is whether the CLL and the PTCL might be clonally related, as is the case with many of the diffuse large B-cell lymphomas arising in CLL patients,12,13,15 although this seems less likely for PTCLs.…”
mentioning
confidence: 98%
“…2 A review of the published cases shows 13 cases of synchronous or metachronous occurrence of B-cell small lymphocytic lymphoma/chronic lymphocytic leukemia (SLL/CLL) and peripheral T-cell lymphoma (PTCL) not otherwise specified (NOS) in the same biopsy specimen (Table 1). [3][4][5][6][7][8][9] Immune dysregulation as a mechanism underlying the simultaneous occurrence of 2 lymphoid malignancies has been proposed, and the chronic stimulation of T-cells by the neoplastic B-SLL clone is a well-documented phenomenon in the literature. 8 HLH is a syndrome of pathological immune activation characterized by severe inflammation and cytokinemia.…”
Section: Introductionmentioning
confidence: 99%